Immune cell profile and metabolic preference following intramuscular lipopolysaccharide injection of highly inbred and advanced intercross genetic lines - Elmore, Kayla M.; Lamont, Susan J.; Bobeck, Elizabeth A. (Frontiers in Veterinary Science, 2025)
Lipopolysaccharide (LPS), a gram-negative bacterial cell wall component commonly used in animal models of inflammation, is also universally found in poultry environments. Documented LPS effects in production animals include reduced feed intake and weight loss; however, research into LPS’s impact on cellular metabolism and immune recovery is limited. This study compared baseline and stressed metabolic phenotypes of peripheral blood mononuclear cells (PBMC) from highly inbred genetic lines and examined fuel preference, cell profiles, and C-reactive protein (CRP) expression at baseline and post-LPS injection. Forty birds from 4 genetic lines (Ghs, Line-8, Sp-21.1, and AIL-F) were randomly assigned to 1 of 2 treatments, receiving intramuscular injections of saline or 1 mg/kg BW LPS (Escherichia coli O55: B5). Body weight was recorded before injection (baseline) and 24 h post-injection (hpi), with cloacal temperature recorded at baseline, 6 hpi, and 24 hpi. Blood was collected at all timepoints for PBMC isolation, metabolic analysis, flow cytometry, and plasma CRP ELISA. Statistical analysis used the SAS 9.4 MIXED procedure with fixed effects of genetic line, injection status, and their interaction followed by Tukey–Kramer adjustment, with significance denoted at p ≤ 0.05. Baseline immune profiles and ATP production varied by line (p ≤ 0.02). LPS did not significantly impact body weight or temperature but influenced all immune cell populations and CRP concentration at 6 hpi (p ≤ 0.02). Sp-21.1 exhibited a glycolytic metabolic profile and higher baseline CD3+CD1.1+ and CD3+CD4+ populations, suggesting enhanced antigen presentation and cytokine signaling. AIL-F displayed sustained monocyte/macrophage activation post-LPS and the highest baseline CD3+CD8α+ populations, indicating a distinct cytotoxic immune response. Line-8 maintained the highest CD3+ populations post-LPS and increased ATP production at 6 hpi, suggesting a balance between immune activation and metabolic compensation. Ghs exhibited a depletion of monocyte/macrophage+ cells post-LPS but later recovered, highlighting a delayed immune response that may impact pathogen resistance. Results suggest genetic line may have a greater influence on metabolic pathway preferences than LPS injection in this experiment. Characterizing metabolic changes during immune activation and recovery may offer insights into breed-specific production traits and inform future breeding and management strategies to enhance health and production efficiency.